Biophysics Week 2026. Biophysics in Ukraine: human energy and willpower in science and education during the wartime - Martynyuk, V. S. (Biophysical Bulletin, 2026)
In March 2026, Ukraine hosted the second annual Biophysics Week — an international event held as part of the global initiative of the American Biophysical Society. This year, the event took on a nationwide scale, with the active participation of the Kyiv, Kharkiv, Lviv, and Zakarpattia branches of the Ukrainian Biophysical Society (UBS), along with leading universities and research institutions of the National Academy of Sciences of Ukraine. Over four days (March 25–28), scientists and young researchers presented reports spanning a broad range of topics, including molecular biophysics, nanotechnology, neural interfaces, bioinformatics, and artificial intelligence applications in biomedicine. Special emphasis was placed on the resilience of the scientific community under wartime conditions, the promotion of biophysics among young people, and the expansion of international collaboration. The strategic priorities of the UBS were defined as engaging youth — in particular through the Junior Academy of Sciences of Ukraine — and strengthening international scientific ties.